COMPUTED TOMOGRAPHY EVALUATION OF DONORS WITHIN PREOPERATIVE PREPARATION FOR LIVING-DONOR KIDNEY TRANSPLANTATION - Mišković, Bojana; Dobrić, Marija; Pavlović, Aleksandar; Maričić, Bojana; Mijović, Ksenija; Jovandić, Biljana; Tomić, Tijana; Vasin, Dragan; Mašulović, Dragan (Srpski medicinski časopis Lekarske komore, 2023)
Kidney transplantation is the therapeutic method of choice in end-stage kidney disease. Preoperative preparation includes a number of examinations, with the radiologists being responsible for accurate imaging evaluation. Computed tomography (CT) is the preferred imaging modality for preoperative renal evaluation and it is the gold standard. Radiological evaluation includes insight into all focal and diffuse diseases of the renal parenchyma, as well as reporting about anatomy, anomalies, the collecting system, and vasculature. A careful insight into the vascular structures of the kidney is possibly the most important step because it helps the surgeon prepare for potential difficulties before the procedure, therefore reducing the risk of potential complications. This is why radiological evaluation of the potential living kidney donor is essential for successful transplantation. The key to accurate radiological reporting is knowledge of surgical techniques and of the difficulties that surgeons may face during the kidney transplantation procedure.